Análisis de los problemas de comportamiento más comunes en los perros de ciudad. - García Moreira, Jehilin Karina (2022)
Attention to behavioral signs is of great importance for pet owners, changes in behavior in pets are not only due to a pathology, in many cases it can be the product of an alteration of the bond between human and animal, the mistreatment, lack of attention, change of diet or habitat of the pet can negatively affect the well-being and animal health, this research has as main objective to collect bibliographic information on the most common problems of behavior and behavior of pets In order to detect the causes and recommend long-term or short-term solutions previously recommended by the corresponding professional (Ethologist), a number of manifestations that dogs experience and that are a headache for their masters were discovered, among which we have: aggressiveness (towards other dogs or people), fear or phobia (of a specific stimulus or general fear c), urination and/or defecation in inappropriate places, destruction, barking, excessive activity and problems related to separation, Most dogs are companion animals, so it is very important that they are quickly trained or treated by the veterinary specialist